Service-Oriented Computing: Agents, Semantics, and Engineering AAMAS 2009 International Workshop, SOCASE 2009, Budapest, Hungary, May 11, 2009, Revised Selected Papers - Kowalczyk, Ryszard; Vo, Quoc Bao; Maamar, Zakaria; Huhns, Michael (Information Systems and Applications, incl. Internet/Web, and HCI, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the International Workshop on Service-Oriented Computing: Agents, Semantics and Engineering, SOCASE 2009, held in Budapest, Hungary, as an associated event of AAMAS 2009, the main international conference on autonomous agents and multi-agent systems. The 10 revised full papers presented were carefully reviewed and selected for inclusion in the book. The papers address a range of topics at the intersection of service-oriented computing, semantic technology, and intelligent multiagent systems, such as: service description and discovery; planning, composition and negotiation; semantic processes and service agents; as well as applications.